2021
DOI: 10.5435/jaaos-d-20-00100
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Spine Biopsy: A Review of the Current Literature

Abstract: Spine lesions are often the result of pathologic processes elsewhere in the body; prompt and accurate diagnosis are crucial to optimize treatment. Despite modern advances in imaging modalities, definitive diagnosis ultimately requires biopsy and histologic analysis. Although open surgical biopsy has traditionally been considered the benchmark, percutaneous image-guided needle biopsy of the spine has proven to be a safe and highly effective method in making a diagnosis. Choosing the optimal biopsy approach, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In clinical practice, imaging-guided spinal biopsies are crucial for the diagnosis and management of spinal infections and malignancies. However, nondiagnostic or inadequate specimen samples are obtained in approximately 8% to 10% of biopsies with adequate preparation and standard operating procedures 7. Several systematic reviews4–6 reported a diagnostic accuracy of 33% to 48% in CT-guided needle biopsy among patients with spinal infections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In clinical practice, imaging-guided spinal biopsies are crucial for the diagnosis and management of spinal infections and malignancies. However, nondiagnostic or inadequate specimen samples are obtained in approximately 8% to 10% of biopsies with adequate preparation and standard operating procedures 7. Several systematic reviews4–6 reported a diagnostic accuracy of 33% to 48% in CT-guided needle biopsy among patients with spinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, nondiagnostic or inadequate specimen samples are obtained in approximately 8% to 10% of biopsies with adequate preparation and standard operating procedures. 7 Several systematic reviews [4][5][6] reported a diagnostic accuracy of 33% to 48% in CT-guided needle biopsy among patients with spinal infections. Therefore, it is necessary to identify imaging findings that can improve the diagnostic accuracy of biopsy in spinal lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations